1999
DOI: 10.1136/vr.144.9.227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the survival of Tritrichomonas foetus in transport, Diamond's and InPouch TF media

Abstract: The abilities of two isolates of Tritrichomonas foetus to survive and replicate in transport and Diamond's medium or in the InPouch TF system (Bio-Med Diagnostics) when exposed to different temperatures for different periods were determined in a series of experiments. Tubes containing thioglycollate transport medium or pouches were inoculated with 4000 to 5000 organisms and kept for up to seven days at 37 degrees C, 22 degrees C, 4 degrees C, or -20 degrees C. When the holding time had elapsed, the numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Other diagnostic procedures include culture of the organism, polymerase chain reaction (PCR), and immunological tests [58][59][60].…”
Section: Diagnosismentioning
confidence: 99%
“…Other diagnostic procedures include culture of the organism, polymerase chain reaction (PCR), and immunological tests [58][59][60].…”
Section: Diagnosismentioning
confidence: 99%
“…Multiple samples were collected from 8 of these bulls for use in this study. Preputial samples were collected by scraping the prepuce with an artificial insemination pipette while applying suction and were inoculated into a thioglycollate transport medium 4 and transported to the laboratory within 1 hour. The samples were centrifuged at 850 ϫ g for 10 minutes and the supernatant removed to leave approximately 0.5 ml or twice the pellet size, whichever was greater.…”
Section: Application Of a Pcr Assay To Enhance The Detection And Idenmentioning
confidence: 99%
“…The T. foetus organisms (field isolate CAPTF 122) were propagated in modified Diamond's medium 4 to provide flagellates for the creation of spiked samples. Samples for extraction from culture medium were prepared by removing 0.1 ml from serial dilutions of a stock solution of T. foetus organisms in culture.…”
Section: Application Of a Pcr Assay To Enhance The Detection And Idenmentioning
confidence: 99%
“…Similar culture results were reported in a previous study. 2 The same study reported that cultures samples kept more than 5 days at 4°C gave negative culture results, stressing the assertion that practitioners and diagnosticians must reduce the period in which samples are maintained at 4°C to less than 3 days. Another study found that pre-storage of samples for up to 5 days at 4°C before qPCR would reduce the sensitivity up to 31%.…”
mentioning
confidence: 99%
“…5,10 However, accurate PCR results correlate with the quality of the sample, which can be affected by transport condition parameters such as temperature and time of transport to the laboratory. The effects of cold temperatures during transport on the survival of T. foetus using different transport media has been investigated previously by light microscope examination 2 and PCR 4 ; however, previous reports did not consider some of the more extreme high temperature conditions present in tropical and subtropical areas of the country or evaluate the effect on PCR.…”
mentioning
confidence: 99%